Les centres de langues : des dispositifs pluriels à un dispositif modélisé ? - Annick Rivens Mompean (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Language centers in French universities have no regular framework of references and normed usage. The needs of the learners are diverse, from languages for general communication to languages for specific purposes (LSP). The structure of the centers, their financial support or pedagogical focus and the type of resources offered are also varied, from face-to-face to distant learning, from multimedia resources to individualized councelling sessions in guided self-learning settings.To create unity through this diversity, we have built a model in order to focus on the recurrent constitutive elements of this specific learning environment. We refer to five general questions that seem essential when we deal with the question of language center: the European context for language learning, the status of the language taught, historical evolution, theories for language learning in particular CALL and autonomous language learning. We then conclude with the bases for a model, that is necessarily evolutive, taking into account the rapid evolution of of these fields of research.